Enjoyment As An Emotional Bridge: Linking Hedonic Motivation To The Intention To Share Social Content On Instagram - Jappy P. Fanggidae; Septia S. Dioh; Liliosa S. Jaiman (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study investigates how hedonic motivation influences users’ intention to share social content on Instagram, focusing on the mediating role of enjoyment of sharing. Grounded in the Uses and Gratifications Theory and Flow Theory, the research proposes that intrinsic enjoyment acts as an emotional mechanism that transforms pleasure-driven motives into prosocial sharing behaviors. Data were collected through an online survey of 162 active Instagram users in Indonesia, aged between 18 and 35 years. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results show that hedonic motivation significantly enhances enjoyment of sharing and directly increases the intention to share social content. Enjoyment of sharing also exerts a strong positive effect on sharing intention and partially mediates the relationship between hedonic motivation and sharing behavior. These findings suggest that self-oriented enjoyment can foster socially valuable participation, indicating that doing good and feeling good can coexist in digital environments. The study contributes to the growing understanding of emotional pathways in social media engagement and offers practical insights for social marketers to design campaigns that are not only meaningful but also enjoyable to share.